Richness and composition of vertebrates in active and inactive latrines of Pteronura brasiliensis (Carnivora, Mustelidae) in the Eastern Amazon, Brazil - Togura, Cintia Massumi; Norris, Darren; Michalski, F. (Iheringia - Serie Zoologia, 2014)
This study aimed to evaluate the richness and composition of the medium and large sized vertebrates in active and inactive latrines of Giant otters [Pteronura brasiliensis (Gmelin, 1788)] in a Sustainable Use conservation unit in the Eastern Brazilian Amazon. The study was performed in 45 latrines along 230 km of the Falsino and Araguari rivers (0°55'N, 51°35'W) and from this total, 24 presented fresh feces of Giant otters while 21 presented only old feces. From July to November 2012 each latrine was continuously monitored with a camera trap set to operate for 24 hours. The effort resulted in 458.8 camera trap/days, with 247.5 camera trap/days in latrines with fresh feces and 211.3 camera trap/ days with old feces. From this effort we obtained photos from a total of 22 vertebrate species. Most species photographed at latrines were mammals (n = 13), followed by birds (n = 6) and reptiles (n = 3). The most frequently photographed species were paca [Cuniculus paca (Linnaeus, 1766), n = 21], ocelot [Leopardus pardalis (Linnaeus, 1758), n = 11], white-tipped dove (Leptotila verreauxi Bonaparte, 1855, n = 8), giant otter [Pteronura brasiliensis (Gmelin, 1788), n = 7], and tapir [Tapirus terrestris (Linnaeus, 1758), n = 6], that accounted for 55.8% of all records. Most records (69.5%) were obtained in latrines with fresh feces and the number of vertebrate species was greater (n = 19) than in latrines with old feces (n = 15). However, the dissimilarity between the vertebrate communities of latrines with fresh and old feces did not differ statistically. However, the mean visitation of vertebrates to latrines with fresh feces was slightly higher than with old feces, although this difference was only marginally significant. There was an increase in records of felids [Leopardus pardalis, Leopardus wiedii (Schinz, 1821), and Panthera onca (Linnaeus, 1758)] in latrines with old feces, but it was only marginally significant. Thus, the presence of fresh feces of giant otters seems to increase the records of vertebrates, being especially important for groups with similar trophic guild.
Riqueza e composição de vertebrados em latrinas ativas e inativas de Pteronura brasiliensis (Carnivora, Mustelidae) na Amazônia Oriental, Brasil